2020
DOI: 10.3389/fmolb.2020.00019
|View full text |Cite
|
Sign up to set email alerts
|

Systematical Analysis of the Cancer Genome Atlas Database Reveals EMCN/MUC15 Combination as a Prognostic Signature for Gastric Cancer

Abstract: Digestive cancers-including gastric cancer (GC), colorectal cancer, hepatocellular carcinoma, esophageal cancer, and pancreatic cancer-accounted for 26% of cancer cases and 35% of cancer deaths worldwide in 2018. It is crucial and urgent to develop biomarkers for the diagnosis, prognosis, and therapeutic benefits of digestive cancers, especially for GC, since the incidence of GC is lower only than lung cancer in China, is hard to detect at an early stage, and is associated with poor prognosis. Mucins, glycopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…We hypothesize that the MUC14/MUC18/MUC15 subgroup could overlap with the different stromal populations. Recent work also showed that the expression levels of MUC14/EMCN , MUC18/MCAM , and MUC15 individually showed significant correlations with worse overall survival in stomach adenocarcinoma (STAD) from TCGA dataset [ 27 ] suggesting that these genes could also be prognostic biomarkers in other digestive cancers. However, this could be specific to gastric cancer since we observed that MUC14 and MUC18 are associated with better survival in the PDAC cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that the MUC14/MUC18/MUC15 subgroup could overlap with the different stromal populations. Recent work also showed that the expression levels of MUC14/EMCN , MUC18/MCAM , and MUC15 individually showed significant correlations with worse overall survival in stomach adenocarcinoma (STAD) from TCGA dataset [ 27 ] suggesting that these genes could also be prognostic biomarkers in other digestive cancers. However, this could be specific to gastric cancer since we observed that MUC14 and MUC18 are associated with better survival in the PDAC cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Two additional atypical endothelial mucins (MUC14/EMCN and MUC18/MCAM) have been described in cancer [ 25 , 26 ]. MUC14, also known as endomucin (EMCN), is an endothelial sialomucin that inhibits endothelial–leukocyte interaction and has been reported to be a poor prognosis marker in gastric cancer [ 27 ]. MUC18 also called melanoma cell adhesion molecule (MCAM) or CD146, is a glycoprotein that is associated with gallbladder cancer and melanoma and that is also detected in pancreatic cancer stroma [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies confirming this role could provide a new molecular mechanism for abnormal angiogenesis and a new target for inhibiting the growth of abnormal blood vessels in clinical tumor therapy. Recently, a systematic analysis of the cancer genome database showed that combined detection of EMCN/MUC15 may be a potential prognostic marker for gastric cancer 31 …”
Section: Discussionmentioning
confidence: 99%
“…Survival data on MUC15 in PDAC from TCGA database also agrees with our results. Dai [ 34 ], analyzing TCGA, also reported that MUC15 combined with EMCN is a prognostic signature for gastric cancer. Because membrane MUC15 in our study was only positive in 37 of 92 samples, we failed to draw a strong conclusion about the relationship between membrane MUC15 and clinicopathological parameters, and larger immunohistochemistry studies are needed to explore its prognostic value.…”
Section: Discussionmentioning
confidence: 99%